Genetic Variability in Immunocompetence and Performance Status of Rhode Island Red Chicken Strains and its Crosses - Das, Ananta Kumar; Kumar, Sanjeev; Rahim, Abdul; Mishra, Anil Kumar (International Journal of Bio-resource and Stress Management, 2023)
The present investigation envisaged to assess genetic variability in immunocompetence and performance traits in three pure strains of Rhode Island Red (RIR) chicken, viz. RIRS, RIRC & RIRW, and its two crosses, viz. CARI-Sonali and CARI-Debendra. A total of 3232, 1263, 346, 1278 and 1258 eggs of RIRS, RIRC, RIRW, CARI-Sonali and CARI-Debendra, were set in three hatches for performance evaluation. Single hatched out 74, 74, 72, 82 and 81 chicks of corresponding genotypes were investigated for immunocompetence status assessed through haemagglutination (HA) test, Lysoplate Assay and Single Radial Immunodiffusion assay. The data on various immunocompetence and performance traits was recorded and analyzed by least squares analysis of variance. The investigation summarized that pure strains demonstrated better immunocompetence than crosses. RIRW demonstrated highest percent fertility followed by RIRC, RIRS, CARI-Sonali and CARI-Debendra. Highest percent hatchability on total egg set basis was observed in RIRC, whereas CARI-Debendra demonstrated highest percent hatchability on fertile egg set basis. CARI-Debendra demonstrated higher body weights than CARI-Sonali followed by RIRS, RIRW and RIRC strains. CARI-Sonali pullets demonstrated (p<0.05) least AFE than RIRS preceded by RIRW, CARI-Debendra and RIRC. Pullets of crosses had (p<0.05) higher EW28 and EW40 than pure strains. CARI-Sonali pullets had (p<0.05) higher EP40 than RIRS>RIRW=CARI-Debendra>RIRC. There had been significant genotype×sex interaction effect on body weights at 2nd, 8th week and onwards. At 2nd week of age, CARI-Debendra-female showed highest body weight but subsequently CARI-Debendra-males were the heaviest. Effects of hatch, sex and chick weight-regression on growth traits as well as of hatch and housing weight-regression on layer production traits were significant. Crosses demonstrated least percent mortality than pure strains during brooding but reverse in laying stage.